«
  
»
X. (x-1) = x. (2x-1) -18


RESOLVENDO

X (x - 1) = x (2x - 1) - 18
x² - x = 2x² - x - 18
x² - 2x² = - x + x - 18
x² = -18

\( x * (x-1) = x * (2x-1) -18 \\ \\ \\ x^2 -x = 2x^2 -x - 18 \\ \\ x^2 -x -( 2x^2 - x - 18) = 0 \\ \\=> -x^2 - 18 \)
Vamos multiplicar por -1 para tirar o sinal de - do 1º termo, não altera o resultado:
\( x^{2} + 18 = 0 \)
Resolvendo por Bháskara:
a=1, b=0, c=18
Δ=b^2−4ac
Δ=(0)2−4*(1)*(18)
Δ=0−72
Δ=−72
\( x = \dfrac{-b \pm \sqrt{\triangle}}{2*a} \\ \\ \\ x = \dfrac{-(0) \pm \sqrt{-72}}{2*1} \\ \\ \\ x = \dfrac{0 \pm \sqrt{72}i}{2} \\ \\ \\ x = \dfrac{0 \pm 6\sqrt{2}i}{2} \\ \\ \\ x’ = \dfrac{0 + 6\sqrt{2}i}{2} \\ \\ \\ x’ = \dfrac{6\sqrt{2}i}{2} \\ \\ \\ x’ = 3\sqrt{2}i \\ \\ \\ x’’ = \dfrac{0 - 6\sqrt{2}i}{2} \\ \\ \\ x’’ = \dfrac{-6\sqrt{2}i}{2} \\ \\ \\ x’’ = -3\sqrt{2}\ i \)
S = {\( 3\sqrt{2}\ i,3\sqrt{2}\ i \)}



TAREFAS SIMILARES: